Towards a theory of action: ontology and politics as foundations of Herbert Marcuse’s dialectical phenomenology - Ferreira de Souza, Juliano Bonamigo (Estudios de Filosofía, 2020)
This article seeks to analyze the modes of composition of the so-called dialectical phenomenology, proposed by Herbert Marcuse in 1928. It is one of his first writings, in which the author seeks to think of a theory of action whose starting point are the historical analyses derived from the historical materialism of Marx and Engels, orchestrated with the existential analytic provided by Being and time, by Heidegger. In order to interpret this pioneering philosophical architecture, (1) we will first show how Marcusean method establishes the understanding of a historical situation. (2) In the second section, we analyze how Marcuse interprets, in a very original way, the ontological aspects of Dasein. (3) In the last part, it is about showing how Marcuse operates a junction of both analyses in order to argue the need for a transforming action on the unveiled social alienation. Together, these three movements seek to emphasize the social concern that has always occupied Herbert Marcuse’s philosophical reflections.